Mapping The Research Landscape of Customer Loyalty on Beauty Clinic Consumers - Vina Islami (Universitas Bina Sarana Informatika, 2024)
Beauty skin care has now become a necessity for everyone who wants healthy skin. The lifestyle of women demands more attention to appearance, for that skin care is very important for everyone. Skin and facial care is one of the main needs of modern women who will support their activities. This need is so noticed by skin health and beauty care service companies, that various skin and facial care clinic businesses have sprung up, especially in big cities. This paper contributes to this field by presenting an analysis of new econometric literature on academic research on customer loyalty in the beauty clinic industry. This method utilizes tools like VOSviewer to visualize and analyze bibliographic data, enabling researchers to identify key concepts, research directions, and emerging trends in a particular field. VOSviewer, a widely used software, helps in mapping relationships between concepts, determining research trends, and providing insights for future studies.sing. This study reviewed the comprehensive Scopus database, analyzing 383 documents to identify key metrics, such as influential publication sources, keywords, countries, affiliations, and authors. The results revealed a growing number of publications related to consumer loyalty.